2022
DOI: 10.3390/cancers14061445
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Proton Therapy for Lung Cancer Patients with Poor Lung Function or Pulmonary Fibrosis

Abstract: PBT has a unique depth–dose curve with a Bragg peak that enables one to reduce the dose to normal lung tissue. We prospectively enrolled 54 patients with non-small cell lung cancer treated with definitive PBT. The inclusion criteria were forced expiratory volume in 1 s (FEV1) ≤ 1.0 L or FEV1 ≤ 50% of predicted or diffusing capacity of the lungs for carbon monoxide (DLco) ≤ 50%, or pulmonary fibrosis. The primary endpoint was grade ≥ 3 pulmonary toxicity, and secondary endpoints were changes in pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The present study found grade ≥ 2 RP in 6 of 50 patients (12%). This is comparable to previous reports on particle therapy for IP-complicated LC, suggesting that our single CIRT is not inferior in safety (Table 6) [10,36,40,41]. In contrast, in our previous report on the same regimen for early-stage LC without IP, none of the 57 patients had G2 or higher pneumonitis [19].…”
Section: Radiation Therapy For Ip-complicated Lcsupporting
confidence: 87%
See 3 more Smart Citations
“…The present study found grade ≥ 2 RP in 6 of 50 patients (12%). This is comparable to previous reports on particle therapy for IP-complicated LC, suggesting that our single CIRT is not inferior in safety (Table 6) [10,36,40,41]. In contrast, in our previous report on the same regimen for early-stage LC without IP, none of the 57 patients had G2 or higher pneumonitis [19].…”
Section: Radiation Therapy For Ip-complicated Lcsupporting
confidence: 87%
“…Among Japanese multicenter retrospective studies, the study on SBRT reported a 3-year OS of 42.6% and that on CIRT 48.2% [33,39]. Other studies have similarly reported relatively poor OS after treatment of IP-complicated LC, regardless of the radiation modality [38,40,41]. Meanwhile, it is clear from several reports that local control of radiotherapy is also reduced in IP-complicated cases [26,40,42,43].…”
Section: Treatment Effectmentioning
confidence: 99%
See 2 more Smart Citations